Controlling of capacity household electricity using ACS758 sensor - Antara, Adi Surya; Suteja, I Wayan arsa; Wiantara Putra, I Gede Eka; Putu Widja, Ida Bagus (Department of Electrical Engineering, University of Patria Artha, 2024)
An electric load monitoring system is a tool designed to monitor and measure electricity usage. The electrical load monitoring process uses a ACS758 model current sensor that connects the electrical load. The microcontroller used is an Arduino Uno microcontroller which functions as the main control system which will be connected to a 16x2 LCD monitor with the aim that in the future it can be monitored in real time and can be read directly on the LCD. By carrying out experiments on assembling the ACS758 sensor module with Arduino Uno which produces a monitoring feature for current measurement readings. The result of this research is a household electricity measurement monitoring system through a prototype made using the ACS758 sensor model with an Arduino Uno which is equipped with a 16x2 LCD monitor to make it easier to monitor the electrical energy load from household electronic devices in the form of current readings and is equipped with a relay module. 5V 1 channel which functions to cut off the current once it exceeds the specified usage limit . The magnitude of the current measurement obtained from the reading of the ACS758 model current sensor will be compared with an ampere meter measuring instrument. By conducting this research, data can be obtained on the percentage of error obtained from the application of the ACS758 sensor, so that later from the results of this experiment the ACS758 sensor will be able to properly and correctly monitor electricity usage and its usage capacity for household loads.